What's the Problem with the Dutch? Andrew Marvell, the Trade Wars, Toleration, and the Dutch Republic. Issue 1 (23rd February 2018) - Zwicker, Steven N.
Abstract : You could be excused for thinking that rather than an Englishman, Andrew Marvell might better have been born a Dutchman in the republic's golden age – an era of religious toleration and commercial ascendance, of fiscal accountability and civic transparency, and of particular brilliance in the painterly arts of landscape and portraiture. There are moments in his career when Marvell seems in thrall to Dutch naval prowess, a strong advocate of confederacy with the States General against the universal monarchy threatened by the French crown, and admiring too of a religious toleration that characterized Dutch society. But that is not the whole story for his 'The Character of Holland' is filled with denial and excoriation, and the contradictions within Marvell's attitude towards England's mercantile rival and religious confederate call out for resolution. This paper explores the ways in which those inconsistencies and contradictions arise from Marvell's apprehensions of sameness and otherness: that the proximity and distance of Britain and the States General is also the story of Marvell's own sense of contradictory selfhood.